Complications associated with the use of mesh to treat female urinary incontinence and pelvic organ prolapse - Blayne Welk; Roger Dmochowski; Kathryn McCarthy; James Keck; Sherif Mourad; Hashim Hashim (Continence)
Complications can result from the use of mesh to treat female stress urinary incontinence or pelvic organ prolapse. While some of these complications are also common to non-mesh-based procedures, the risk of vaginal exposure of mesh, or mesh extrusion into other pelvic organs are unique complications that must be considered when using mesh. Chronic pain after mesh-based procedures can be a difficult complication to manage and may occur. Patients with stress incontinence or prolapse that are considering surgical treatment should be counseled on the potential complications and the likelihood of them occurring. Although there has been focus on the development, introduction and regulation of mesh, the diagnostic clinical decision-making process has not been put under scrutiny, and likely significantly impacts patient outcomes. There is a need to develop patient reported outcome measures for mesh procedures, and further work is needed to create a standardized way to measure and communicate different types of mesh-related complications. Future research to focus on the diagnostic clinical decision making process is recommended, including education on the ‘whole journey’ of the patient during the perioperative pathway.